Modulating NAD+ metabolism, from bench to bedside. (7th August 2017) - Katsyuba, Elena; Auwerx, Johan
Abstract: Discovered in the beginning of the 20 th century, nicotinamide adenine dinucleotide (NAD + ) has evolved from a simple oxidoreductase cofactor to being an essential cosubstrate for a wide range of regulatory proteins that include the sirtuin family of NAD + ‐dependent protein deacylases, widely recognized regulators of metabolic function and longevity. Altered NAD + metabolism is associated with aging and many pathological conditions, such as metabolic diseases and disorders of the muscular and neuronal systems. Conversely, increased NAD + levels have shown to be beneficial in a broad spectrum of diseases. Here, we review the fundamental aspects of NAD + biochemistry and metabolism and discuss how boosting NAD + content can help ameliorate mitochondrial homeostasis and as such improve healthspan and lifespan. Abstract : As part of our focus series on metabolism, this review discusses the physiological role of NAD + and the potential therapeutic effects of increasing NAD + levels.